2019
DOI: 10.1111/desc.12843
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ intentionally communicative vocalizations elicit responses from caregivers and are the best predictors of the transition to language: A longitudinal investigation of infants’ vocalizations, gestures and word production

Abstract: What aspects of infants’ prelinguistic communication are most valuable for learning to speak, and why? We test whether early vocalizations and gestures drive the transition to word use because, in addition to indicating motoric readiness, they (a) are early instances of intentional communication and (b) elicit verbal responses from caregivers. In study 1, 11 month olds (N = 134) were observed to coordinate vocalizations and gestures with gaze to their caregiver's face at above chance rates, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 67 publications
8
93
2
Order By: Relevance
“…In recent research with typically developing, typically hearing infants, researchers have identified specific early communicative behaviors as being theoretically important indicators of readiness for language learning and good empirical predictors of later language development. 2,[23][24][25][26][27] Positive predictors include the frequency with which infants produce give gestures, show gestures, index-finger pointing, and communicative vocalizations (operationalized as vocalizations made within 1 second of looking to the caregiver's face). Alongside first words, these behaviors are thought to be positive predictors because they indicate social-cognitive readiness for language development, and because they elicit timely and informative caregiver responses, which are known to scaffold further development.…”
Section: The Relationship Between Early Pragmatic Skills and Later Lamentioning
confidence: 99%
See 4 more Smart Citations
“…In recent research with typically developing, typically hearing infants, researchers have identified specific early communicative behaviors as being theoretically important indicators of readiness for language learning and good empirical predictors of later language development. 2,[23][24][25][26][27] Positive predictors include the frequency with which infants produce give gestures, show gestures, index-finger pointing, and communicative vocalizations (operationalized as vocalizations made within 1 second of looking to the caregiver's face). Alongside first words, these behaviors are thought to be positive predictors because they indicate social-cognitive readiness for language development, and because they elicit timely and informative caregiver responses, which are known to scaffold further development.…”
Section: The Relationship Between Early Pragmatic Skills and Later Lamentioning
confidence: 99%
“…Indeed, the frequency with which infants rely on some other gestures (eg, openhand pointing) is a negative predictor of language development. 25,27 Thus, when assessing early pragmatic development in DHH infants, it has become apparent that investigating precise frequencies of specific infant naturalistic behaviors is important.…”
Section: The Relationship Between Early Pragmatic Skills and Later Lamentioning
confidence: 99%
See 3 more Smart Citations